Hubungan Sistem Pembelajaran Daring dengan Minat Belajar Bahasa Arab Siswa Mts Nuril Huda Tarub Grobogan - Parhan, Parhan; Syafii, mohamad (STAINI Press, 2023)
The problem in this study is that there are still students who don't have a smartphone, and there are even parents who feel burdened with internet costs or increasing credit which makes it difficult for students to follow the learning process. This can affect students' interest in learning Arabic. so that it can be predicted that online learning has a close relationship in determining student learning interest. This study aims to find out and test empirical data related to the relationship between online learning systems and interest in learning Arabic. In this study the authors used a quantitative method with a correlational approach to quantitative data obtained from the research object, namely class VIII students at MTs Nuril Huda Tarub Grobogan. The sample of this research was 125 respondents from a total population of 182 students. Data collection was carried out using a questionnaire / questionnaire technique. The type of analysis used is a simple correlation analysis which is described descriptively. The results of this study are that there is a positive and significant relationship between online learning and interest in learning Arabic in class VIII MTs Nuril Huda Tarub Grobogan. This is shown by the strength of influence or the correlation coefficient of 0.7234 at the 95% confidence level (α = 0.05), while the magnitude of the influence or coefficient of determination Kp is 0.5184 which means that online learning has an influence on interest in learning Arabic by 52% and means the remaining 48% is determined by other factors. For the significance test, a tcount value of 11.4 is obtained, which means that there is a significant relationship between online learning and interest in learning Arabic